2006
DOI: 10.1158/0008-5472.can-05-2856
|View full text |Cite
|
Sign up to set email alerts
|

The High-Affinity IgG Receptor, FcγRI, Plays a Central Role in Antibody Therapy of Experimental Melanoma

Abstract: We examined the role of Fc;R in antibody therapy of metastatic melanoma in wild-type and different Fc;R knockout mice. Treatment of B16F10-challenged wild-type mice with TA99 antibody specific for the gp75 tumor antigen resulted in a marked decrease in numbers of lung metastases. Treatment of individual Fc;R knock-out mice revealed the high-affinity IgG receptor, Fc;RI (CD64), to represent the central Fc;R for TA99-induced antitumor effects. The potential of immunemodulating agents to further enhance the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 20 publications
9
92
0
Order By: Relevance
“…The similar specific binding activity of the mAb P and mAb M BR55-2 to CD64 (FC␥RI) assumes importance because CD64 interaction with Fc of the mAb is essential for IgG-dependent phagocytic and ADCC activities (23)(24)(25). Moreover, it is known that Fc␥RI is the essential receptor for antibody therapy in a mouse melanoma model (26).…”
Section: Discussionmentioning
confidence: 99%
“…The similar specific binding activity of the mAb P and mAb M BR55-2 to CD64 (FC␥RI) assumes importance because CD64 interaction with Fc of the mAb is essential for IgG-dependent phagocytic and ADCC activities (23)(24)(25). Moreover, it is known that Fc␥RI is the essential receptor for antibody therapy in a mouse melanoma model (26).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that IFN␥ could increase the expression of Fc␥RI in AML cells, which led at one point to the exploration of IFN␥ treatment combined with drug-conjugated anti-Fc␥RI antibody as a potential therapy for AML (17). However, Fc␥RI is not only a candidate therapeutic target; it is also a major effector of phagocytosis in myeloid cells (16,18,19). Hence, we tested the possibility that IFN␥ treatment not only would increase Fc␥RI expression, but would also enhance the phagocytic ability of AML cells.…”
Section: Ifn␥ Increases Fc␥ri Expression and Phagocytic Ability Inmentioning
confidence: 99%
“…Antibody-dependent killing of tumor cells by neutrophils in the absence of G-CSF is described to be nonexistent or weak (16,17) and is likely mediated through FcgRIIa (18). Therefore, specific targeting of FcgRI has been proposed, as this may overcome potential inhibitory signals through FcgRIIb when IgG mAbs are employed (19).…”
Section: Most Clinically Used Mabs Belong To the Igg Subclass And Thementioning
confidence: 99%